2019
DOI: 10.1002/14651858.cd012533.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Telephone interventions, delivered by healthcare professionals, for providing education and psychosocial support for informal caregivers of adults with diagnosed illnesses

Abstract: This is a repository copy of Telephone interventions, delivered by healthcare professionals, for providing education and psychosocial support for informal caregivers of adults with diagnosed illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 231 publications
0
27
0
2
Order By: Relevance
“…Telephone intervention enables healthcare professionals to verbally communicate remotely with caregivers. In specific, interventions using combined in-person tele-support technology have been previously designed and successfully implemented for caregivers of chronically ill elderly patients including PD which judged as acceptable, easy to learn and user-friendly by caregivers [53,54] .…”
Section: Discussionmentioning
confidence: 99%
“…Telephone intervention enables healthcare professionals to verbally communicate remotely with caregivers. In specific, interventions using combined in-person tele-support technology have been previously designed and successfully implemented for caregivers of chronically ill elderly patients including PD which judged as acceptable, easy to learn and user-friendly by caregivers [53,54] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an early decision was that the research intervention would be implemented via telephone sessions. Telephone delivery had been found successful in previous EOLPC studies (Corry et al, 2019; Forbes & Bryant, 2020) and is preferred by patients with advanced disease (Mosher et al, 2019; Piamjariyakul et al, 2013; Vitacca et al, 2019). All participants signed informed consent to participate.…”
Section: Methodsmentioning
confidence: 99%
“…Another systematic review of 21 trials found that telephone interventions providing support for caregivers may slightly reduce anxiety and improve preparedness to care, but did not significantly improve other caregiver outcomes. 16 None of the included trials in this review measured changes in HRQOL 16 and both reviews recommended further high-quality trials in caregiver populations. Recent qualitative research conducted with caregivers of older adults discharged from hospital indicated that negative impacts of caregiving at this time can stem from feelings of uncertainty exacerbated by gaps in formal support, the strain of balancing caregiving with other life demands and a sense of helplessness.…”
Section: Open Accessmentioning
confidence: 98%
“…[10][11][12][13] In addition to problems faced by caregivers in providing ongoing care, there is limited evidence about how to effectively support caregivers of older adults when they are discharged from hospital, including what interventions can sustain and improve caregivers' health and well-being. [14][15][16] Older adults discharged from hospital are at high risk of functional decline, unplanned hospital readmissions and injurious falls. [17][18][19] This transition can be particularly problematic for older adults who receive care support and their caregivers.…”
Section: Open Accessmentioning
confidence: 99%